Genetic Criticism and the Creative Process : Essays from Music, Literature, and Theater - Jones, Joseph E.; Kinderman, William (Book collections on Project MUSE., 2009)
The term "genetic criticism" or "critique genetique" relates not to the field of genetics, but to the genesis of works of art, as studied in a broad and inclusive context. The essays in this volume explore aspects of genetic criticism in an interdisciplin.